Crowdsourcing in Management Research : A New Tool for Scientific Inquiry - Lenart-Gansiniec, Regina (Taylor & Francis, 2024)
Crowdsourcing in Management Research explores the evolving landscape of academic research in the context of contemporary legal, social, cultural, and technological shifts. The book delves into the intricate processes and challenges associated with managing crowdsourcing initiatives in science. It sheds light on the essential competencies required by those initiating crowdsourcing projects, offering practical insights for effective implementation. Furthermore, the text explores the future directions of crowdsourcing in science, considering the influence of emerging technologies such as blockchain, digital storytelling, gamification, metaverse, augmented reality, and artificial intelligence. As one of the few comprehensive resources available, the book serves as a valuable guide for scholars, researchers, and graduate students interested in crowdsourcing paradigms. It emphasizes accessibility by avoiding unnecessary jargon and caters to non‑specialist readers, including booksellers and librarians. The geographical and temporal relevance of the work is underlined, providing a contemporary perspective on the subject. The inclusion of well‑known and topical case studies enhances the book’s relevance, while groundbreaking content ensures its significance in the rapidly evolving field of management research. The Open Access version of this book, available at www.taylorfrancis.com , has been made available under a Creative Commons Attribution‑Non Commercial‑No Derivatives 4.0 license.